Integrating Green Overall Equipment Effectiveness (G-OEE) and Reduce Strategies: A Transformation Toward Sustainable Cigarette Manufacturing - Sulistyowati, Enik; Hamidah, Nur; Riyana, Iis (Journal Knowledge Industrial Engineering (JKIE), 2026)
The cigarette manufacturing sector currently faces a dual mandate: maximizing production efficicency while drastically reducing its environmental footprint. Traditional Overall Equipment Effectiveness (OEE) metrics often fail to capture ecological dimension, creating a significant measurement gap in sustainable performance. This study addresses this limitation by developing and validating an Integrated Green Overall Equipment Effectiveness (G-OEE) model. By embedding the "Reduce" principle of the Circular Economy (CE) into the classic OEE framework, this research provides a nuanced evaluation of manufacturing operations in East Java. Employing a mixed-methods approach, the study analyzed quantitative data from January 2025 to March 2026, encompassing Availability, Performance, Quality, and Reject rates. The proposed G-OEE model expands the traditional APQ pillars by integrating three critical Green Performance Factors: energy efficiency (GPF1), material utilization (GPF2), and a waste reduction index (GPF3). Findings reveal a striking disparity: while conventional OEE averaged 82.74%, the G-OEE score dropped to 62.20%. This gap effectively exposes hidden environmental inefficiencies that standard metrics typically overlook. The regression validation (R² = 0.89, RMSE = 3.2%) confirms the model’s high predictive validity, establishing G-OEE as a practical decision support tool for production managers. Ultimately, the G-OEE framework enables manufacturers to align Lean efficiency with Circular Economy responsibilities through a single, simultaneous monitoring tool.